Money, Meat, and Inflation : Using Price Data to Understand An Export Shock in Sudan - Ramcharan, Rodney (IMF Working Papers; Working Paper, 2002)
Sudanese inflation dramatically fell in 2000. But just prior to the sharp decline, an export ban was placed on Sudanese livestock. Motivated by this clue, and in the absence of any reliable income or employment data, this paper systematically develops simultaneous models of the consumer price index (CPI) and the exchange rate to assess the economic impact of the export ban. It finds that livestock exports play a large economic role as an important source of income and as a store of value. In the long run, livestock exports are positively associated with nonfood inflation. In the short run, food price movements are negatively associated with livestock exports: to help smooth income, lower food prices generate increased livestock exports. Therefore, unable to export livestock, farmers may have flooded the local market with meat, lowering food prices. Moreover, the loss of income and the decline in wealth lowered aggregate demand, leading to the decline in nonfood prices.